Pengaruh Gaya Kepemimpinan, Motivasi Dan Disiplin Kerja Terhadap Kinerja Pegawai Badan Diklat Dan Litbang Pemerintah Daerah Kabupaten Sragen - Ramsi, Aliga, Drs. Yuli Tri Cahyono , M.M., Akt., CA (2015)
The research aims to examine and analyze the influence of leadership style motivation and work discipline toward performance of employee in Badan Diklat dan Litbang Pemerintah Daerah Kabupaten Sragen. Data collected through distribution of questionnaires and it is implemented to Badan Diklat dan Litbang Pemerintah Daerah Kabupaten Sragen's 77 employees. Analysis of data in this research using the help of SPSS version 15. A sampling technique uses a census method and data test technique is used within the research includes validity test by factor analysis, reliability test with cronbach. Classic assumption test and double linear regression analysis, to verify and to prove the research hypothesis. Analysis result demonstrates that leadership, motivation, and work discipline style (statistically) have a siignificant influence toward employee performance.